Eimeria species in young and adult sheep raised under intensive and/or semi-intensive systems of a herd from Umuarama city, Parana State, Brazil - Zanetti Lopes, Welber Daniel; Borges, Fernando de Almeida; Faiolla, Thais de Paula; Antunes, Liliane Tada; Lino Borges, Dyego Goncalves; Rodriguez, Fernando de Souza; Ferraro, Gisela; Teixeira, Weslen Fabricio [UNESP]; Maciel, Willian Giquelin [UNESP]; Felippelli, Gustavo [UNESP]; Costa, Alvimar Jose da [UNESP]; Pereira, Valdomiro; et al. (Univ Federal Santa Maria, 2013)
The present study aimed to identify Eimeria species in young and adult sheep raised under intensive and / or semi-intensive systems of a herd from Umuarama city, Parana State, Brazil using the traditional diagnostic methods and to correlate the infection level/types of infection in the different age/system in this herd. Fecal samples were collected from the rectum of 210 sheep and were subjected to laboratory analysis to differentiate the species. Furthermore, animals were observed to determine the occurrences of the clinical or subclinical forms of eimeriosis. Out of the 210 collected fecal samples, 147 (70%) were positive for Eimeria oocysts, and 101 (47.86%) belonged to young animals that were raised under intensive and / or semi-intensive farming systems. Oocysts from 9 species of Eimeria parasites were identified in the sheep at the following prevalence rates: E. crandallis, 50.0%; E. parva, 21.6%; E. faurei, 8.1%; E. ahsata, 8.1%; E. intricata, 5.4%; E. granulosa, 2.7%; E. ovinoidalis, 2.0%; E. ovina, 1.3%; and E. bakuensis, 0.6%. There were no differences regarding the more frequent Eimeria species among the different ages of animals or between the different farming management systems. Based on these data, E. crandallis was the most prevalent, followed by E. parva and E. faurei species, regardless of the age. Higher parasitism was diagnosed in the young animals that were raised in a confinement regime, and the disease found in the herd was classified as subclinical. Further studies should be conducted in this herd, to verify if the eimeriosis subclinical can cause damage especially in young animals with a high level of infection.
Keywords: coccidia; eimeriosis; ooPG; sheep